Two Accessory Proteins Govern MmpL3 Mycolic Acid Transport in Mycobacteria - Allison Fay; Nadine Czudnochowski; Jeremy M. Rock; Jeffrey R. Johnson; Nevan J. Krogan; Oren Rosenberg; Michael S. Glickman (mBio, 2019)
ABSTRACT Mycolic acids are the signature lipid of mycobacteria and constitute an important physical component of the cell wall, a target of mycobacterium-specific antibiotics and a mediator of Mycobacterium tuberculosis pathogenesis. Mycolic acids are synthesized in the cytoplasm and are thought to be transported to the cell wall as a trehalose ester by the MmpL3 transporter, an antibiotic target for M. tuberculosis. However, the mechanism by which mycolate synthesis is coupled to transport, and the full MmpL3 transport machinery, is unknown. Here, we identify two new components of the MmpL3 transport machinery in mycobacteria. The protein encoded by MSMEG_0736/Rv0383c is essential for growth of Mycobacterium smegmatis and M. tuberculosis and is anchored to the cytoplasmic membrane, physically interacts with and colocalizes with MmpL3 in growing cells, and is required for trehalose monomycolate (TMM) transport to the cell wall. In light of these findings, we propose MSMEG_0736/Rv0383c be named “TMM transport factor A”, TtfA. The protein encoded by MSMEG_5308 also interacts with the MmpL3 complex but is nonessential for growth or TMM transport. However, MSMEG_5308 accumulates with inhibition of MmpL3-mediated TMM transport and stabilizes the MmpL3/TtfA complex, indicating that it may stabilize the transport system during stress. These studies identify two new components of the mycobacterial mycolate transport machinery, an emerging antibiotic target in M. tuberculosis. IMPORTANCE The cell envelope of Mycobacterium tuberculosis, the bacterium that causes the disease tuberculosis, is a complex structure composed of abundant lipids and glycolipids, including the signature lipid of these bacteria, mycolic acids. In this study, we identified two new components of the transport machinery that constructs this complex cell wall. These two accessory proteins are in a complex with the MmpL3 transporter. One of these proteins, TtfA, is required for mycolic acid transport and cell viability, whereas the other stabilizes the MmpL3 complex. These studies identify two new components of the essential cell envelope biosynthetic machinery in mycobacteria.